Asirtmali Aba Wrestling in Turkish sports history and culture - Haci Sahın (Selcuk University, 2014)
Aşırtmalı Aba Wrestling, which is one of the wrestling types that is made with wearing clothes, expresses itself as an outward reflection of spiritual and physical needs of people as a whole both in previous times and today.  It also faces us as a cultural accumulation of Turkish people in their daily lives and values within social dimensions. In other words, practicing wrestling in times when Turks have lived in Central Asia has grown out of the need for the unity of spiritual sentiments and thoughts with body by remaining bound to their living standards and cultural norms of those times. In this research the traditional wrestling of Turks, aşırtmalı aba wrestling, which is performed in Gaziantep, has been analyzed with its historical background, clothing, rules and techniques. In the research, terminologies have been noticed which originated from aşırtmalı aba wrestling and gradually gained technical meanings and contributed to the enrichment of the language. Aşırtmalı aba wrestling receives its name from clothing made by aba, a loose-fitting garment woven of camel or goat hair, which pehlivan, a wrestler of Turkish traditional wrestling, has worn as well as from technical term called 'el aşırma', an act performed by the attacker to grab the belt of his opponent in the back by moving his hand over opponent's shoulder and reaching his hand to opponent's belt in the back. Aşırtmalı aba wrestling is performed in Gaziantep province, especially at the end of harvest, in weddings, festivals and celebrations.  Basic games/techniques, which are performed so often in Aşırtmalı aba wrestling, are shown step by step in pictures.  With this study, which aşırtmalı aba wrestling is introduced and comparisons are made between forms of this wrestling among other Turkic Republics, you will have the view of Turkish world. The fundamental aim of this study is to present the historical development of aşırtmalı aba wrestling, its terminology, clothing, rules and basic games/techniques which is performed in Gaziantep. These issues, which have been lacking in previous studies, will be filled in this study and therefore, it will constitute weight for the research. In this research, historical and descriptive methods have been used; literature scan and method of interviewing experts in collecting data about aba wrestling have been employed.  Since it is widely performed in Gaziantep, an on-site survey has been done by visiting the province.